EFL/ESL learners language related episodes (LREs) during performing collaborative writing tasks. - Abu Bakar, Kamariah; Abd. Samad, Arshad; Baki, Roselan; Mahmoudi, Leila (Academy Publisher, 2013)
This paper examined how the homogeneous dyads-- two EFL (i.e. Iranian) dyads and two ESL (i.e., Malaysian) dyads--consciously reflected on their language in the course of performing collaborative writing tasks. To this end, the dyads were asked to do fifteen writing tasks collaboratively. The pair talk was audio-recorded and transcribed for each dyad. It was revealed that EFL/ESL dyads had different orientations towards metatalk; EFL dyads tended to focus considerably more on meta-linguistic features of language than ESL dyads. The findings are discussed with a reference to the different status of the English language in the two contexts of Iran and Malaysia (i.e., EFL vs. ESL) as well as the effect of previous educational experiences of the learners. The findings of the study could be of pedagogical help and significance to educationists and practitioners.